Dynamics and control of electric transmission and microgrids - Padiyar, K. R.; Kulkarni, Anil M. (John Wiley & Sons, Inc., 2019)
"Highlights the role of transmission and distribution grids that ensure the reliability and quality of electric power supply. - Original coverage of Analysis and Control of Loss of Synchronism including, Extended Equal Area Criterion (EEAC). - Timely and unique coverage of On-Line Detection of Loss of Synchronism, Wide Area Measurements and Applications, Wide-Area Feedback Control Systems for Power Swing Damping and Microgrids-Operation and Control. Market description (Please include secondary markets) Primary: Senior undergraduate and Ph. D. students on courses relating to power system dynamics and control/ electrical power industry professionals working on the planning, design and development of controls for enhancing grid performance. Secondary: Researchers in R & D laboratories connected with modernization and systems improvement of electricity supply systems"--Provided by publisher